Perspective on Industrial Electrification and Utility Scale PV in the Arctic Region - Asplund, Anton; Nilsson, Lars J. (International Journal of Sustainable Energy Planning and Management, 2024)
Two concurrent trends may fundamentally change how we understand the role of solar PV at high latitudes. Until now, relatively low annual insolation in combination with low electricity demand during the summer months has not favoured PV in the Arctic. However, continued decreases in costs for PVs in combination with increasing electricity demand from industrial electrification is quickly changing the situation. Net-zero climate targets necessitates industrial decarbonisation and low-cost electricity from solar and wind facilitates emission reductions through electrification and hydrogen. While research on PV in the Arctic so far has focused on off-grid and community scale systems, in this perspective article we explore the prospects for utility scale PV in Northern Scandinavia. Research usually identifies regions endowed with rich sun and wind resources at lower latitudes as promising locations for electricity intensive industries. We calculate the levelized-cost-of-electricity for utility scale PV to be 51 EUR/MWh based on recent data and this cost is likely to be below 35 EUR/MWh before 2030 considering the projected continued reduction of the levelized cost of electricity for PV. This makes utility scale PV a highly viable future option to complement wind and hydro in meeting the very large forecasted future electricity demands from the steel industry, data centres, and power-to-X production above the Arctic circle from 2030 and onwards.